Implementasi Kurikulum Merdeka Pada Pembelajaran PAI di SDN Purisemanding 1 Jombang - Erisa, Nina; Sirojuddin, Didin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The study aims to analyze the implementation of the independent curriculum in Islamic Religious Education (PAI) learning at SDN Purisemanding 1 Jombang. The Focus of the study covers three main aspects, namely: (1) Planning, implementation, and evaluation of the implementation of the independent curriculum, (2) constraints in the implantation of the independent curriculum in PAI learning, (3) efforts made to overcome obstacles in the implementation of the independent curriculum in PAI learning. The study used a qualitative descriptive approach, with daya collection techniques in the form of interviews, observations, and documentation. Informants involved in this study included the prinical, deputy curriculum, PAI Teachers, and Student. The data obtained were analyzed using data presentation, and conclusions. The results of the study showed that: (1) planning the implementation of the independent curriculum in PAI learning was carried out by upgrading teacher skills by participating in training; implementation of learning began learning whith greetings an prayers, learning refers to learning Modules, learning refers ti the Problem Based Learning (PBL) method; evaluation was carried oud using formative assessment and summative assessment. (2) the obstacles faced were limited book facilities and learning media, and different student understandings. (3) efforts made to overcome the obstacles that occur include providing oral questions and daily tests, and forming study groups.